A study to investigate state of ethical Development in E-learning - Muhammad, AbdulHafeez; MD. Ghalib, Mohd. Feham; Ahmad, Farooq; Naveed, Quadri N; Shah, Asadullah (Science and Information (SAI) Organization, 2016)
Different researchers evidenced that e-learning has provided more opportunities to behave unethically than in traditional learning. A descriptive quantitative enquiry-based study is performed to explore same issue in e-learning environment. The factors required for ethical development of students were extracted from literature. Later, efforts are made to assess their significance and their status in e-learning with 5-point Likert scale survey. The sample consisted of 47 teachers, 298 students, and 31 administrative staff of e-learning management being involved in e-learning. The work also observed state of students on various ethical behaviors. The study emphasized that physical presence of teacher, an ethically conducive institutional environment, and the involvement of the society members are among the main factors that help in the ethical development of a student which are missing in e-learning. The results of the study showed that the moral behavior of e-learning is at decline because of lack of these required factors in e-learning. This work also suggested the need of a model indicating how these deficiencies can be addressed by the educational institutions for ethical development of higher education learners.